Clinical aspects and white blood cell count in children with urinary tract infection - Hendrik B. Tokan; Komang Kari (Paediatrica Indonesiana, 1999)
The purpose of this study was to evaluate the clinical aspects and to count white blood cells in attempt to flnd simple parameters to predict urinary tract infection (UTI) prospectivecaly. Twenty four children with pyuria were studied, the history of clinical symptoms of urinary tract infection and blood leucocyte count were obtained. Local symptoms was the commonest symptom found in this study (87.5%), followed by fever (75.0%). If urine culture was taken as the gold standard, the predictive value of positive local symptoms with pyuria to urinary tract infection was 76.19%, sensitivity 88.88% and specificity 16.66%. The predictive value of history of fever with pyuria ti urinary tract infection was 76.47"10, sensitivity 72.22% and specificity 33.33%. The predictive value of leucocytosis with pyuria to urinary tract infection was 76.47%, sensitivity 72.22% and specivicity 33.33%. Meaning that the local symptoms, fever or leucocytosis with pyuria were not a good tool for the diagnosis of urinary tract infection, but probably useful as a screening procedure to distinguish the posibility of urinary treat infection.